1985
DOI: 10.1152/ajprenal.1985.249.4.f582
|View full text |Cite
|
Sign up to set email alerts
|

Lack of intramembranous particle clusters in collecting ducts of mice with nephrogenic diabetes insipidus

Abstract: We suggested previously, on the basis of indirect evidence, that in two strains of mice with nephrogenic defects of urinary concentration the deficiency arose from an inadequate rise in water permeability of the collecting duct system. In this study we tested the question further by assuming that the frequency of intramembranous particle (IMP) clusters seen by freeze-fracture can be used as a morphological marker of vasopressin-induced water permeability. Three genotypes of mice were studied: 1) DI +/+ Severe,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…To conclude, this investigation extends the earlier observation [1,2] that ADH stimulation of rat collecting ducts causes the appearance of particle aggregates in apical membrane coated pits. Our studies are the first to demonstrate directly that increased apical membrane endocytosis occurs via coated pits in rabbit cortical collecting duct following removal of ADH from the peritubular bathing medium.…”
Section: Discussionsupporting
confidence: 90%
“…To conclude, this investigation extends the earlier observation [1,2] that ADH stimulation of rat collecting ducts causes the appearance of particle aggregates in apical membrane coated pits. Our studies are the first to demonstrate directly that increased apical membrane endocytosis occurs via coated pits in rabbit cortical collecting duct following removal of ADH from the peritubular bathing medium.…”
Section: Discussionsupporting
confidence: 90%
“…However, the fact that many apical FITC‐positive vesicles were unstained for AQP2 indicates that at least a portion of the apical AQP2 in these cells is able to escape endocytosis and remain at the cell surface. The amount of apical endocytosis and the degree of co‐localization with AQP2 was variable from cell to cell, indicating a cellular heterogeneity in the water permeability response of principal cells that has been suggested previously based on freeze‐fracture studies (Brown et al, 1985). This implies that, under conditions of ad lib .…”
Section: Discussionmentioning
confidence: 58%
“…1 shows the osmotic water flow across bladders that were stimulated with ADH in the absence ofan osmotic gradient, followed by imposition ofdifferent hypotonic mucosal solutions to produce a series of transepithelial osmotic gradients. In those bladders subjected to large osmotic gradients, the initial 12 high rate of water flow was rapidly attenuated. As anticipated, those bladders exposed to smaller osmotic gradients had a proportionally lower initial rate of ADH-stimulated water flow.…”
Section: Resultsmentioning
confidence: 99%
“…A large body of evidence indicates that particle aggregates are closely correlated with or are themselves water channels responsible for the increase in apical membrane water permeability induced by ADH (reviews 8, 9). Freeze-fracture electron microscopy has also revealed that distinctive intramembrane particle structures are closely correlated with ADHinduced permeability changes in the apical membrane of the mammalian collecting duct (10)(11)(12).…”
Section: Introductionmentioning
confidence: 98%